2021
DOI: 10.1007/s10163-021-01281-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights into hazardous solid waste generation during COVID-19 pandemic and sustainable management approaches for developing countries

Abstract: The recent emergence of the COVID-19 pandemic has contributed to the drastic production and use of healthcare and personal protective equipment, leading to the release of a huge quantity of hazardous medical and solid wastes in the environment. Meanwhile, these solid wastes may contribute to the spread of the SARS-CoV-2 viral particles when disposed of without proper treatment and care. Since SARS-CoV-2 could persist on different material surfaces including plastic, steel, paper, cardboard, cloth, and wood, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The reuse of effluent, sludge, or biosolids has been recognized as an effective strategy to address the scarcity of water shortage through crop irrigation and to supplement the depleted essential nutrients in the soil. However, recent evidence of the prevalence of SARS-CoV-2 RNA on the effluents and sludge samples indicate potential associated environmental, ecological, and health risks on the use of these environmental materials, if they are not properly decontaminated or effectively treated from the novel virus before usage ( da Silva et al, 2020 , Adelodun et al, 2021a ). Indeed, the detection of a high load of SARS-CoV-2 RNA in river water due to direct sewage disposal in low sanitation regions and effluents of wastewater treatment plants is an indication of environmental and public health safety concerns in rural settings ( Guerrero-Latorre et al, 2020 ).…”
Section: Consequences Of Sars-cov-2 Contamination In Effluents Sludge...mentioning
confidence: 99%
See 1 more Smart Citation
“…The reuse of effluent, sludge, or biosolids has been recognized as an effective strategy to address the scarcity of water shortage through crop irrigation and to supplement the depleted essential nutrients in the soil. However, recent evidence of the prevalence of SARS-CoV-2 RNA on the effluents and sludge samples indicate potential associated environmental, ecological, and health risks on the use of these environmental materials, if they are not properly decontaminated or effectively treated from the novel virus before usage ( da Silva et al, 2020 , Adelodun et al, 2021a ). Indeed, the detection of a high load of SARS-CoV-2 RNA in river water due to direct sewage disposal in low sanitation regions and effluents of wastewater treatment plants is an indication of environmental and public health safety concerns in rural settings ( Guerrero-Latorre et al, 2020 ).…”
Section: Consequences Of Sars-cov-2 Contamination In Effluents Sludge...mentioning
confidence: 99%
“…Although some studies reported the absence of SARS-CoV-2 RNA from both wastewater effluent and produced sludge, it is recommended that environmental samples, including wastewater and sludge generated from the hospitals or designated centers for tendering to the COVID-19 patients, should be disposed of following the guidelines of hazardous waste and incineration ( Ji et al, 2020 , Adelodun et al, 2021a ).…”
Section: Challenges Associated With Virus Inactivation and Removal In...mentioning
confidence: 99%
“…Based on existing studies, improper waste management failing to adhere to standard operating procedures for solid waste rooted from the flaws in the existing waste management systems, which is commonly observed in low resource settings and could be a critical aspect in this regard (UNEP, 2020a). Inadequacy in legislations and policies, mechanization and automation, technical knowledge, infrastructure, staff, safety measures, awareness and monitoring were observed during the COVID-19 outbreak that could contribute to the anticipated risk of SARS-CoV-2 infectivity from solid waste sector ( Oruonye and Ahmed, 2020 ; Adelodun et al, 2021 ; Acharya et al, 2021 ; Falih et al, 2021 ; Zand and Heir, 2021 ). Scarcity of financial support and technical knowledge for waste-management are the major bottlenecks for developing countries ( Sharma et al, 2020 ; Acharya et al, 2021 ).…”
Section: Solid Wastementioning
confidence: 99%
“…Scarcity of financial support and technical knowledge for waste-management are the major bottlenecks for developing countries ( Sharma et al, 2020 ; Acharya et al, 2021 ). Only just over half of the countries in the world have any form of legislation in place regarding healthcare waste management and only about a quarter have dedicated laws ( Oruonye and Ahmed, 2020 ; UNEP, 2020a; Adelodun et al, 2021 ; Chand et al, 2021 ; Falih et al, 2021 ). Waste management systems are designed for steady state flow with low variations generally, particularly in low-middle income countries waste sector is largely ignored and untreated as an essential service due to political and economic constraints ( Acharya et al, 2021 ; Faisal et al, 2021 ; Goswami et al, 2021 ).…”
Section: Solid Wastementioning
confidence: 99%
“…Similarly, on the insights into hazardous solid-waste generation during COVID‑19 pandemic and sustainable management approaches for developing countries established that waste management in most developing countries still lack adequate management practices and required harmonious gap [ 27 ]. The study therefore recommends segregation of solid waste from source of generation.…”
Section: Introductionmentioning
confidence: 99%